2021
DOI: 10.1186/s12888-021-03291-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the working experiences at frontline of COVID-19 pandemic and mental health of Korean public health doctors

Abstract: Background Demographic, work environmental, and psychosocial features are associated with mental health of healthcare professionals at pandemic frontline. The current study aimed to find predictors of mental health for public health doctors from working experiences at frontline of COVID-19 pandemic. Methods With first-come and first-served manner, 350 public health doctors with experiences of work at COVID-19 frontline participated online survey on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 62 publications
(108 reference statements)
4
25
0
Order By: Relevance
“…Such fear might drive stigmatizing behaviors among the public and relatives (e.g., avoidance toward their acquaintances and neighbors who worked as healthcare workers) (Stangl et al, 2019). The finding has been in line with studies on healthcare workers in Bangladesh (Khan et al, 2021), Korea (Han et al, 2021), and the US (Hennein et al, 2021), implying that such phenomenon might be culturally universal. In addition, it is noteworthy that nurses who worked in the "dirty team" were more likely to report a higher level of perceived stigma.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Such fear might drive stigmatizing behaviors among the public and relatives (e.g., avoidance toward their acquaintances and neighbors who worked as healthcare workers) (Stangl et al, 2019). The finding has been in line with studies on healthcare workers in Bangladesh (Khan et al, 2021), Korea (Han et al, 2021), and the US (Hennein et al, 2021), implying that such phenomenon might be culturally universal. In addition, it is noteworthy that nurses who worked in the "dirty team" were more likely to report a higher level of perceived stigma.…”
Section: Discussionsupporting
confidence: 77%
“…Not surprisingly, we found that different aspects of COVID-19 worries (including worries of contracting COVID-19, family members being infected with COVID-19 from participants' nursing duties, insufficiency of personal protection equipment at workplace) were independently contributing to anxiety symptoms among the nurses in Hong Kong. Similar findings have been reported in healthcare workers in other countries, including China (Zhang et al, 2021), Korea (Han et al, 2021), and the US (Hennein et al, 2021). Providing nurses with safe and secure work environments and sufficient supply of personal protective equipment is required for protection of mental health among nurses coping with the pandemic.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In total, 507 of 597 students (84.9%), higher percentage of response than other recent studies for medical students (34) or public health doctors (35) during COVID-19 pandemic, responded to the questionnaire. After excluding data for 53 students with missing values, our final dataset included deidentified responses from 454 medical students (123 in the first year of medical school, 110 in the second year, 121 in the third year, and 100 in the fourth year) at Seoul National University College of Medicine during June and July of 2020.…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 74%